2014
DOI: 10.1002/adv.21475
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Characterization of Coaxial Electrospun Poly(ε‐Caprolactone)/Gelatin Nanofibers for Biomedical Applications

Abstract: Coaxial poly(ε-caprolactone) (PCL)/gelatin nanofibers were successfully fabricated by electrospinning, using 2,2,2-trifluoroethanol (TFE) as a solvent. The morphology of the PCL/gelatin coaxial fibers was evaluated using attenuated total reflectance Fourier transform infrared (FTIR) spectroscope, scanning electron microscope, and transmission electron microscope. The disappearance of gelatin absorption bands in FTIR spectrum after the mat washing step suggested that coaxial nanofibers were obtained. The coaxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
2
4
0
1
Order By: Relevance
“…Next, it decreased after getting a maximum at an intermediate voltage around 15 kV (1.51 µm average diameter at 13 kV, 1.76 µm at 15 kV and 1.62 µm at 17 kV). This non-monotonic effect of the voltage on the fiber diameter has previously been observed for polymers of a different nature [ 33 , 34 , 35 ]. It was also observed that the higher the voltage, the higher the variability in fiber diameter (standard deviation: 0.14 µm at 13 kV, 0.20 µm at 15 kV and 0.26 µm at 17 kV).…”
Section: Resultssupporting
confidence: 66%
“…Next, it decreased after getting a maximum at an intermediate voltage around 15 kV (1.51 µm average diameter at 13 kV, 1.76 µm at 15 kV and 1.62 µm at 17 kV). This non-monotonic effect of the voltage on the fiber diameter has previously been observed for polymers of a different nature [ 33 , 34 , 35 ]. It was also observed that the higher the voltage, the higher the variability in fiber diameter (standard deviation: 0.14 µm at 13 kV, 0.20 µm at 15 kV and 0.26 µm at 17 kV).…”
Section: Resultssupporting
confidence: 66%
“…As expected, the typical absorption bands of gelatin were detected in ATR-FTIR spectra of all samples, i.e. the characteristic peak at: 1632 cm -1 , related to the stretching vibration of C=O bond (amide I); 1540 cm -1 related to the C-N stretching vibrations (amide II) and N-H bending vibrations; 1238 cm -1 describing the CH2 wagging vibrations (amide III); and at 3288 cm -1 regarding the N-H stretching vibration [92][93][94][95][96]. Other than gelatin-related bands, characteristic absorption bands of the PCL phase could also be identified in electrospun and UV-cured samples at 2949 cm -1 and 2865 cm -1 (regarding the asymmetric CH2 stretching and symmetric CH2 stretching, respectively), at 1727 cm -1 (describing the carbonyl stretching C=O associated with the ester bonds), at 1226 cm 4= (related to the C-O and C-C stretching) and at 1185 cm -1 (regarding the asymmetric COC stretching) [97][98][99].…”
Section: Elucidation Of Chemical Compositionmentioning
confidence: 99%
“…For the electrospinning of Ge, lowtoxic alternative solvents have also been considered, including acetic acid [53], [54] or ethylacetate/acetic acid in water [55]. Specifically, the formic/acetic mixture has been considered as a suitable candidate for the electrospinning of PCL/Ge scaffolds [56]- [59].…”
Section: Introductionmentioning
confidence: 99%